(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
The study addresses low student participation and communication anxiety in EFL speaking classes. It emphasizes the global need for communicative competence and promotes interactive methods role-plays, discussions, debates, and group tasks to improve fluency and confidence. Based on classroom observations and student feedback, it proposes a model combining motivation, collaboration, and real-life contexts. Findings show that such strategies greatly enhance engagement and speaking skills.